EFEKTIVITAS KOMPENSASI PELENGKAP UNTUK PENINGKATAN KINERJA KARYAWAN (STUDI PADA PDAM TIRTA MUKTI KABUPATEN CIANJUR) - kendra Nur Ghibrani; Acep Samsudin; Nor Norisanti (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
The provision of trapping compensation is very positive applied in a company, and is designed not only for the benefit of employees but also for the benefit of the company, among others for employees to prevent problems arising from employees such as employee turnover and absenteeism. Companies must be able to carry out positive policies so that existing employees are encouraged to develop and improve employee performance in terms of quality and quantity, so that they are able to meet the demands of work that ultimately achieves the company's goals. This research uses quantitative methods. The research population is the employees of PDAM Tirta Mukti. The population is sixty respondents in PDAM Tirta Mukti. The ups and downs in employee performance at PDAM Tirta Mukti are affected by complementary compensation while others are influenced by other variables. Have a positive and significant effect between the relationship of pencer compensation on employee performance. The results of the complementary compensation t test partially affect the performance of employees at PDAM Tirta Mukti.